Effects of gas-phase collisions on particles rapidly desorbed from surfaces - Ibrahim Ali , Noorbatcha; Lucchese, Robert R.; Zeiri, Yehuda (The American Physical Society, 1987)
The influence of postdesorption collisions on the experimentally measured angular and energy distributions of the rapidly desorbed molecules is investigated using direct Monte Carlo simulation procedures. By simulating the desorption of NO from LiF(100), we find that the postdesorption collisions have a significant effect on the final angular, rotational energy, and translational energy distributions of the desorbed molecules.